Alteration of Type I Collagen in the Radial Artery of Patients With End-Stage Renal Disease. (April 2015) - Bai, Yaling; Zhang, Junxia; Xu, Jinsheng; Cui, Liwen; Zhang, Huiran; Zhang, Shenglei
Abstract: Background: Cardiovascular disease is the leading cause of death in chronic kidney disease. Extracellular matrix remodeling is implicated in atherosclerosis development. This study investigated the effects and possible mechanism of type I collagen expression on radial artery elasticity in patients with end-stage renal disease (ESRD). Methods: Sixty-five patients receiving forearm arteriovenous fistula in the Fourth Hospital of Hebei Medical University from January 2010 to December 2012 were enrolled in the study. The echo-tracking technique was used to measure radial artery 1-point pulse wave velocity (PWVβ), and immunohistochemical staining was used to detect the expression of type I collagen and transcription factor CBFA1, a marker for calcification, in the radial artery. Uremic serum and serum from healthy volunteers of different concentrations were then used to treat the rat aortic vascular smooth muscle cells (VSMCs), reverse transcription polymerase chain reaction (PCR) was used to measure COL1A1 and CBFA1 transcription and a Western blot was performed to detect type I collagen expression in the rat aortic VSMCs. Results: In patients with ESRD, increased COL1A1 expression was an independent risk factor for radial artery PWVβ ( P < 0.05) and was positively associated with that of CBFA1 (r = 0.573, P < 0.001). In the rat aortic VSMCs, serum from patients with ESRD upregulated COL1A1 and CBFA1 transcription as well as type I collagen expression in a concentration-dependent manner ( P < 0.05). Conclusions: Type I collagen expression is an essential factor for radial artery elasticity dysfunction in patients with ESRD. Uremic toxins apparently induced a phenotypic transition of the rat aortic VSMCs, leading to increased type I collagen secretion and subsequent extracellular matrix remodeling.